Risk taking, attributions and serious occupational accidents - Finnish Institute of Occupational Health, Helsinki; Salminen, Simo (Helsinki, 1997)
"The doctoral thesis examined the effect of risk taking and attributions to serious occupational accidents. Based on the literature on accident theories, attribution theories, and risk taking, six hypotheses were presented and tested."